Corporate Social Responsibility, Corporate Governance and Earnings Quality: Evidence from Korea. (9th June 2013) - Choi, Bo Bae; Lee, Doowon; Park, Youngkyu
Abstract: Manuscript Type: Empirical Research Question/Issue: How does corporate governance affect a manager's intention to promote corporate social responsibility (CSR)? Is the relationship between financial transparency and CSR activities affected by the business group affiliation and ownership structure of firms? Research Findings/Insights: CSR ratings are negatively correlated with the level of earnings management when all firms are considered. However, the relationship is weaker for chaebol firms and firms with highly concentrated ownership, which suggests that CSR practices can be abusively used by those firms to conceal their poor earnings quality. The adverse use of CSR is discouraged if the fraction of shares owned by institutional investors is high. However, no evidence is found for a similar moderating effect for foreign investors. Theoretical/Academic Implications: This study suggests that the business group affiliation and the ownership structure of a firm are important factors in determining the managerial incentives to engage in CSR, which can explain the mixed results reported in previous research. In addition, the possibility of a simultaneous relationship between CSR and other key firm characteristics, such as earnings quality, should be considered when conducting research on CSR. Practitioner/Policy Implications: This study provides the insight to investors and other stakeholders that the managerial incentives behind CSR activities can differ depending on a firm's characteristics. Care must be taken when assessing the CSR activities, in particular, of firms with weak corporate governance. For policy makers, it is important to ensure that CSR‐related disclosures by firms are based on actual plans and are not intended to deceive stakeholders, especially when the firms are not actively monitored by external shareholders.